Load Frequency Control by Quadratic Regulator Approach with Compensating Pole using SIMULINK - Saeed, Zubair; Ur Rehman, Haseeb; Haseeb, Abdul; Taseen, Rabia; Shah, Muhammad Shahzaib; Shaikh, Inam Ul Hasan; Haider Ali, Muhammad Zulqarnain (JAREE (Journal on Advanced Research in Electrical Engineering), 2023)
In this research, for the load frequency control (LFC) challenge, we provide a few possible approaches to building an optimum PID controller. This scheme employs the Quadratic Regulator Approach with Compensating Pole (QRAWCP) approach. In both multi-area and single-area power systems, this control law is used to solve load frequency concerns. And the other scenario that is considerable, the controller's robustness is evaluated on the same systems in terms of non-linearities, external disturbances, and parametric uncertainty such as the Governor Dead Band (GDB) as well as the Generation Rate Constraint (GRC). The performance of the control method is evaluated using Simulink simulations.